2018
DOI: 10.1002/cncr.31775
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiovascular disease risk and risk factors among women with and without breast cancer

Abstract: Background: Cardiovascular disease (CVD) risk is an important health concern among breast cancer survivors. However, few studies have examined whether trajectories of CVD risk and major risk factors are worse among women with a breast cancer diagnosis than those without. Methods: We compared changes in weight, body mass index (BMI), waist circumference, systolic blood pressure, and 10-year CVD risk between women with (N=813) and without (N=1049) an incident breast cancer diagnosis while enrolled in the Siste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The average 10-year probability of CVD in relation to the cancer type was significantly higher in patients with hepatic, colon, lung, breast, and gastric cancer [ 29 ]. On the other hand, FRS was not significantly higher among those with breast [ 30 ], testicular [ 31 ], childhood cancer [ 32 ], or ovarian cancer [ 33 ] compared with controls. The current analysis, which demonstrated increased odds of elevated 10-year ASCVD risk among participants with a history of bladder or kidney, prostate, colorectal, lung, melanoma, testicular, and other cancer, suggests that ASCVD risk estimation may be more clinically relevant for individuals diagnosed with specific cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The average 10-year probability of CVD in relation to the cancer type was significantly higher in patients with hepatic, colon, lung, breast, and gastric cancer [ 29 ]. On the other hand, FRS was not significantly higher among those with breast [ 30 ], testicular [ 31 ], childhood cancer [ 32 ], or ovarian cancer [ 33 ] compared with controls. The current analysis, which demonstrated increased odds of elevated 10-year ASCVD risk among participants with a history of bladder or kidney, prostate, colorectal, lung, melanoma, testicular, and other cancer, suggests that ASCVD risk estimation may be more clinically relevant for individuals diagnosed with specific cancers.…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Cancer Institute, certain treatments can damage the heart and the circulatory system leading to a series of side effects, such as hypertension, abnormal heart rhythm and heart failure, which are generally caused or exacerbated by chemotherapy and radiotherapy [50]. No studies currently exist that analyze how rowing affects heart function and blood pressure in BC survivors, but there are several articles showing that physical exercise improves these functions [37,[51][52][53][54][55][56]. Notable among them is the study by Stefani et al [51] which reports that BC survivors who received chemotherapy treatment experienced a significant improvement in diastolic function measurements after four years of dragon boat training, increasing by 2.5 cm/s.…”
Section: Introductionmentioning
confidence: 99%
“…However, we lacked information about the specific chemotherapy regimens received by the patients. Cardiovascular disease is the leading cause of death for women with ductal carcinoma in situ or stage I disease, and for women aged > 80 years with stage II disease [ 9 ]. A recent systematic review found that women with a history of breast cancer have a higher risk of breast cancer mortality than their cancer-free counterparts [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that women with a history of breast cancer have a higher risk of breast cancer mortality than their cancer-free counterparts [ 10 ]. However, in the National Institute of Environmental Health Sciences Sister Study Cohort, changes over time in cardiovascular disease risk, adiposity measures, and blood pressure were similar between women who developed an incident breast cancer and those who did not [ 9 ].…”
Section: Discussionmentioning
confidence: 99%